2019
DOI: 10.5204/ssj.v10i3.1418
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Whole Student: Integrating Wellness Education into the Academic Classroom

Abstract: College students are increasingly reporting higher stress, which can negatively influence their personal and intellectual development. Greater academic challenges and new social experiences in college may be accompanied by stressors like mental health issues, family concerns, or financial pressures. To help students manage stress, institutions typically provide resources through health services, student life or student affairs, recreation departments, or other entities that operates primarily outside the acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…7 Students are most often of a healthy physical and euthymic state as they embark on their studies during their HE career. 6,8 The World Health Organization (WHO) revealed that mental health accounts for 13% of the global disease burden, and that suicide is the second leading cause of death amongst 15-29-year-olds. 9 The HE students are part of the most vulnerable group when considering issues of mental health, emotional disorders, and psychological problems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Students are most often of a healthy physical and euthymic state as they embark on their studies during their HE career. 6,8 The World Health Organization (WHO) revealed that mental health accounts for 13% of the global disease burden, and that suicide is the second leading cause of death amongst 15-29-year-olds. 9 The HE students are part of the most vulnerable group when considering issues of mental health, emotional disorders, and psychological problems.…”
Section: Introductionmentioning
confidence: 99%
“…12 During the first few months of university, depression and anxiety related signs and symptoms increase, particularly for female students. 6,8 A previous study conducted on Psychology, Medicine, Dentistry and Nursing students identified that 52% of students suffer from some degree of depression: 25% suffer from mild depression, 19% from moderate depression and an alarming 8% of study participants suffered from major depression. 13 A more recent study on anxiety and depression concluded that medical students scored 61% higher for anxiety and 70% higher for depression during, what they call, the coronavirus disease 2019 (COVID-19) era.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this premise, educators argue that the university curriculum is the metaphorical glue that holds the student experience together and therefore the most efficient context for fostering student wellbeing (e.g., Baik et al, 2017;McInnis, 2001). They embed new initiatives to support wellbeing within curricula with impressive outcomes (e.g., Johnson et al, 2019). For example, the work by Craig Hassed and colleagues has demonstrated the effectiveness of embedding programs and mindfulness training within tertiary programs (e.g., Hassed et al, 2009;Lo, Francis-Cracknell & Hassed, 2017).…”
Section: Introductionmentioning
confidence: 99%